Rheology of acid suspensions containing cassava bagasse: Effect of biomass loading, acid content and temperature - Polachini, Tiago Carregari [UNESP]; Mulet, Antonio; Cárcel, Juan A.; Telis-Romero, Javier [UNESP] (Elsevier, 2019)
Understanding the characterization and rheological behavior of acid suspensions of cassava bagasse provides essential information for the design of conversion processes. Samples with different cassava bagasse concentrations (0–10% w∙w−1), phosphoric acid (0–10% w∙w−1) at temperatures between 278.13 and 318.13 K were submitted to steady-state flow over a wide range of shear rates (1–265 s−1). The biomass particles had considerable residual starch (~50% db), low lignin content and adequate particle size (<200 μm) for the conversion process. Flow curves were well-fitted to the Herschel-Bulkley model, presenting a Newtonian domain at low solids and acid content and a non-Newtonian behavior with noticeable yield stress and shear-thinning characteristic (n < 1) at above 6% of cassava bagasse. Resistance to flow increased as the solids loading and acid content increased. Temperature dependence could be expressed as a function of an Arrhenius-type equation with good accuracy of fit.
Keywords: Apparent viscosity; Arrhenius-type equation; Herschel-Bulkley model; Lignocellulose; Residual starch; Shear-thinning